Gender Balance in Companies’ Management: The Effect on Financial Indicators - T. O. Razumova; E. S. Ivanova (Управленческие науки)
The purpose of this paper is to calculate the effect of gender balance in management on the economic performance of Russian companies. The relevance of the topic is explained by the fact that in Russia women make up almost 50% of the workforce (that exceeds the indicators of Western Europe and North America) and get a higher education on an equal basis with men, but women’s participation in the governing bodies of companies is insignificant (about 5%). This could result the companies losing the benefits of women’s human capital. The paper hypothesizes that Russian public joint stock companies with gender balanced governing bodies have better financial performance. An econometric model has been used to test this method. Data for the period of 9 years (from 2010 to 2018) for 44 non-financial companies whose shares were traded on the stock exchange during this period are taken. There has been applied Tobin’s Q as an indicator of the financial performance. Since there is a two-tier management system in public joint-stock companies in Russia. Two councils are considered as the governing bodies of the company — the supervisory board and the board of directors. The result of the study is the absence of a significant relationship between the gender balance in the governing bodies and the financial success of the companies. The main reasons for the lack of significant results include a special industry profile of Russian companies. The recommendation for the following studies is to focus not just on the firm’s financial performance but on the corporate and social impact of gender balance either.